Theory of State in the Political Philosophy of Avicenna Relying on Spragens' Methodology - Ahmad Jahaninasab; Kamal Poladi; Saeed Eslami (‫سیاست متعالیه‏, 2021)
The purpose of the present study is to explain the theory of state in the political philosophy of Avicenna in order to display the way of presenting a favorable government in terms of political issues based on Spragens' methodology. In this regard, by delving deep into the political ideas and doctrines of Avicenna, it was attempted to answer this main question: How does Shaykh al-Ra'is (Avicenna) think of a favorable political system? Thus, the present research is compiled in four parts investigating problems, causes, goals, and solutions. The method of study is historical-descriptive and the results convey that Avicenna's political philosophy has an integrated intellectual-philosophical system including the social nature of human beings, the necessity of a prophet's leadership due to his connection with demiurge, and the necessity of prophethood in politics. In presenting his approach to statism and proposing the theory of state, Avicenna deems that the best system is the prophetic political model in which a prophet or his successor is at the center of affairs. In fact, the theory of state in Avicenna's political philosophy has been based upon the divine nature of humans and the utmost role of government in people's prosperity and salvation in both worlds.